2021
DOI: 10.1016/j.radcr.2021.09.045
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of torsion and infarction of an extralobar pulmonary sequestration with MR, CT, and surgical correlation

Abstract: Extralobar pulmonary sequestration is a rare congenital pulmonary malformation that may present early in life or remain asymptomatic. Here we present a case of torsion of an extralobar pulmonary sequestration on its vascular pedicle. Although the patient's initial symptomatology suggested intraabdominal pathology, the correct preoperative diagnosis was determined in large part by the lesion's MRI characteristics, which strongly suggested tissue infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 21 publications
0
11
1
Order By: Relevance
“…The left/right ELS ratio was 1:2 in our centre’s cases. The proportion of ELS on the right side was larger in our study, while previous literature found that ELS tended to occur on the left side [ 4 7 ], which may be one of the reasons for the low preoperative diagnosis rate. In our cases, one child was an adolescent, three were school age, and two were preschool age.…”
Section: Discussioncontrasting
confidence: 75%
See 4 more Smart Citations
“…The left/right ELS ratio was 1:2 in our centre’s cases. The proportion of ELS on the right side was larger in our study, while previous literature found that ELS tended to occur on the left side [ 4 7 ], which may be one of the reasons for the low preoperative diagnosis rate. In our cases, one child was an adolescent, three were school age, and two were preschool age.…”
Section: Discussioncontrasting
confidence: 75%
“…In the past 14 years, a total of 32 cases of ELS were diagnosed in our hospital, of which only 6 cases were combined with torsion of the vascular pedicle, accounting for 18.75% of cases. To date, a total of 13 paediatric cases of ELS with torsion have been reported in the English literature [ 4 6 , 8 17 ]. To the best of our knowledge, this is the largest number of cases reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations